0153 Patient-Defined Insomnia Severity: How Much Wakefulness is Problematic?. (27th May 2020) - D'Antonio, B; Boyle, J T; Seewald, M; Giller, J; Muench, A; Vargas, I; Williams, N J; Klingman, K; Perlis, M L
Abstract: Introduction: While Insomnia Disorder is formally defined in the ICSD-3 and DSM-5, neither diagnostic system adopts quantitative criteria for illness severity. Interestingly, quantitative criteria are provided for frequency and chronicity (i.e., ≥ 3 days / week for ≥ 3 months). For research purposes, illness severity has long been defined using the "30 minute rule" (SL and/or WASO and/or EMA of ≥ 30 minutes is the threshold for clinical relevance). In the present analysis, this threshold was assessed for its significance to patients. Methods: Sleep continuity disturbance (SCD; SL, WASO, and EMA) and problem endorsement data were collected from an archival/community-based sample (N = 4680; 60% female; Ages 18–89 years; www.sleeplessinphilly.com ). Problem endorsement was evaluated through questions that included, "Do you consider this a problem?" after participants reported length of SL, WASO, and EMA. Problem endorsement percentages were calculated for 5 minute bins for between 0 and 65 minutes, with one additional bin for > 65 minutes. The temporal bins were compared for significant deviations using absolute (percent of subjects at 0–5 and 5–10 minutes) and moving references (last significant percent). Results: The first temporal bin to differ from the absolute reference for SL, WASO, and EMA was the 26–30 minute bin. At this threshold, 87%, 70%, and 94% of the subjects' identifying SL, WASO and EMA as being problematic (and was deemed statistically different from "normal" [0–10 minute values]). Conclusion: These data suggest that the "30 minute rule" (which is of unknown provenance) roughly corresponds to the level of illness severity (lowest common threshold) identified by patients as problematic. While the threshold for SL and EMA show a clear majority, the lower percentage of subjects for WASO suggests that people are more tolerant of middle of the night wakefulness. Support: